Insulin Contributes to Fine-Tuning of the Pancreatic Beta-Cell Response to Glucagon-Like Peptide-1 - Moon, M.J., Korea University, Seoul, Republic of Korea; Kim, H.Y., Korea University College of Medicine, Seoul, Republic of Korea; Park, S.M., Korea University, Seoul, Republic of Korea; Kim, D.K., Korea University, Seoul, Republic of Korea; Cho, E.B., Korea University, Seoul, Republic of Korea; Hwang, J.I., Korea University, Seoul, Republic of Korea; Seong, J.Y., Korea University, Seoul, Republic of Korea (Molecules and cells, 2011)
Glucagon-like peptide-1 (GLP-1) stimulates insulin secretion from pancreatic β-cells in a glucose-dependent manner. However, factors other than glucose that regulate the β-cell response to GLP-1 remain poorly understood. In this study, we examined the possible involvement of insulin and receptor tyrosine kinase signaling in regulation of the GLP-1 responsiveness of β-cells. Pretreatment of β-cells with HNMPA, an insulin receptor inhibitor, and AG1478, an epidermal growth factor receptor inhibitor, further increased the cAMP level and Erk phosphorylation in the presence of exendin-4 (exe-4), a GLP-1 agonist. When β-cells were exposed to a high concentration of glucose (25 mM), which stimulates insulin secretion, exe-4-induced cAMP formation declined gradually as exposure time was increased. This decreased cAMP formation was not observed in the presence of HNMPA. HNMPA was able to further increase the exe-4-induced insulin secretion when β-cells were exposed to high glucose for 18 h. Treatment of β-cells with insulin significantly decreased exe-4-induced cAMP formation in a dose-dependent manner. Lowering the phospho-Akt level by HNMPA or LY294002, a PI3K inhibitor, further augmented exe-4-induced cAMP formation and Erk phosphorylation. These results suggest that insulin contributes to fine-tuning of the β-cell response to GLP-1.